PSYCHOLOGICAL CAPITAL AND PRINCIPAL LEADERSHIP STYLE ON THE TEACHER'S PERFORMANCE IN INDONESIAN MADRASAH: JOB SATISFACTION AS A MEDIATOR - Masdianah, Masdianah; Syahid, Achmad; Saloom, Gazi; Moormann, Peter Paul (Psikis : Jurnal Psikologi Islami, 2023)
Madrasah principals and teachers become an entry point for policy to address disparities in student achievement and quality of madrasahs in Indonesia. Unfortunately, not many studies have tested the theoretical model of teacher job satisfaction as a mediator of the influence of teacher psychological capital and principal leadership style on teacher performance. The population of this study was public and private madrasah teachers in Malang Regency, East Java, Indonesia. At the same time, the research sample consisted of 356 teachers selected by the purposive sampling method. The measuring tool uses the Psychological Capital Questionnaire (PCQ-24), the Multifactor Leadership Questionnaire (MLQ)-5X, and the Job Satisfaction Survey (JSS). Testing construct validity used confirmatory factor analysis (CFA), while data analysis used Structural Equating Modeling (SEM) with Mplus 7.4 software. The results of SEM show that the theoretical model of teacher job satisfaction as a mediator variable in the influence of teacher psychological capital and leadership style of madrasah principals on teacher performance fit the empirical data. The results also show that teacher job satisfaction mediates the effect of teacher psychological capital and principal leadership style on teacher performance, but the direct effect of the two independent variables on the dependent variable is stronger.